2014
DOI: 10.1213/ane.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Lidocaine Decreases Tumor Necrosis Factor Alpha Expression Both Locally and Systemically in Pigs Undergoing Lung Resection Surgery

Abstract: Our results suggest that lidocaine can prevent OLV-induced lung injury through reduced expression of proinflammatory cytokines and lung apoptosis. Administration of lidocaine may help to prevent lung injury during lung surgery with OLV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…It has been suggested that IV lidocaine may have beneficial perioperative effects. [33][34][35][36][37] We hypothesized that tumescent infiltration without liposuction produces a serum lidocaine concentration-time profile resembling a constant IV infusion lasting 12 to 16 hours or more. Furthermore, we hypothesized that liposuction removes significant amounts of lidocaine before it can be systemically absorbed.…”
mentioning
confidence: 99%
“…It has been suggested that IV lidocaine may have beneficial perioperative effects. [33][34][35][36][37] We hypothesized that tumescent infiltration without liposuction produces a serum lidocaine concentration-time profile resembling a constant IV infusion lasting 12 to 16 hours or more. Furthermore, we hypothesized that liposuction removes significant amounts of lidocaine before it can be systemically absorbed.…”
mentioning
confidence: 99%
“…The subsequent clinical amelioration and marked improvement on the SPECT functional imaging validated this decision. Finally, the patient's persisting head pain was addressed by the non-invasive SPG block [21,22,34].…”
Section: Discussionmentioning
confidence: 99%
“…PSE injections induce tumor necrosis factor (TNF)-alpha modulation directly to the central nervous system and act to normalize the inflammatory response in stroke, traumatic brain injury, and encephalopathic conditions [18][19][20]. The SPG is known to decrease migraine intensity [21] and also to have an anti-inflammatory effect [22]. We thus aimed to provide information about the use of novel anti-inflammatory procedures, in a step-wise approach, for the treatment of a patient with disabling, treatment resistant, neuropsychiatric comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Local anesthetics have shown to be potent inhibitors of inflammation, reduce edema formation in various conditions (Winning et al, 2012;Garutti et al, 2014). The anti-inflammatory effect of local anesthetics has not been totally elucidated, but it should possess a wide range of anti-inflammatory actions through their effects on cells of the immune system, as well as microorganisms, thrombocytes leukocytes and erythrocytes (Ohsaka et al, 1994;Cassuto and Tarnow 2003;Lan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory effect of local anesthetics has not been totally elucidated, but it should possess a wide range of anti-inflammatory actions through their effects on cells of the immune system, as well as microorganisms, thrombocytes leukocytes and erythrocytes (Ohsaka et al, 1994;Cassuto and Tarnow 2003;Lan et al, 2005). Garutti et al (2014) confirm the anti-inflammatory effect of lidocaine. The authors reported that the expression tumor necrosis factor α (TNF-α) decreased after systemic administration.…”
Section: Introductionmentioning
confidence: 99%